Impact of Netspeak on the Writing Skills of Generation X and Generation Y - Tahir, Rameen; Hassan, Fiza (Journal of Communication and Cultural Trends, 2021)
This research focuses on the impact of netspeak on the formal writing skills of the users. It is labelled as the hub of slang and informal language content by many experts. The current analysis accounts for five objectives including the identification of the prime causative factors responsible for deviation in the use of the standard variety, the appliance of the impact of Netspeak on formal writing, the nature of its impact (positive or negative), the assessment of its impact with reference to age and on the basis of the kind of response netspeak receives from the living generations, determining its sustainability. The objectives are attained through a questionnaire, collecting responses from the individuals belonging to Generation X and Generation Y. This study proposes that the influence of mother tongue and code switching are the prime causative factors of netspeak. The research further showcases the impact of the electronic variety on the users’ formal writing skills which can disturb their formal linguistic framework; however, the variety on its own has been indicated previously as a handy tool for the users. Focusing on the factor of age neutrality, the current study suggests that although Generation X is more inclined towards the use of the standard variety, yet it remains quite open-minded towards the existence and usage of the new variety on social media, stating it to be a “feature of the progressive world”. The research reflects the enthralling nature of netspeak which has massively contributed to its popularity. It was inferred that neither the platform (the digital world) is losing its power nor the users are in the mood of giving up on it in the near future. It can be said that it’s a budding variety for the people by the people, born to live, thus strengthening the sustainability argument. Keywords: Computer-Mediated Communication (CMC), Generation X, Generation Y, Language 1 (L1), Language 2 (L2), millennial, netspeak